Etnomatematika: Persamaan Garis Lurus dengan Media Geogebra - Rezkiyana Hikmah; Retno Nengsih (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2021)
The development of GeoGebra media is a technology contribution to the education's world, especially mathematics. The use of GeoGebra media and  its association with egrang game aim to instill the concept of parallelism, perpendicularity, crossing, and slope of the line. This study aims to see how the students mathematics understanding ability is and whether the enhancement of it by using Geogebra media is better than ordinary learning. The samples were students in grade VIII  at SMPN 1 Cibinong in 2019/2020. The number of samples is 60 students. This research is a quasi-experimental research design with a non–equivalent control group. The instrument was a test (pretest and posttest)  to see the n gain of understanding ability. Data were analyzed using the Mann-Whitney test. The results are students mathematics understanding ability with Geogebra is not better than without Geogebra and the enhancement of it by using Geogebra media  is  better than without Geogebra media at SMPN 1 Cibinong in 2019/2020. Keywords: GeoGebra Media, Ethnomathematics, Understanding Ability